2019
DOI: 10.1194/jlr.m090845
|View full text |Cite
|
Sign up to set email alerts
|

Dysferlin deficiency alters lipid metabolism and remodels the skeletal muscle lipidome in mice

Abstract: ized by the onset of muscle weakness and loss of function usually in the late teens and with slow progression (2). Dysferlinopathies include limb-girdle muscular dystrophy type 2B and Miyoshi myopathy, with the proximal and distal limb-girdle muscles being the main muscles affected (2-4). Mouse models of dysferlinopathy harboring dysferlin deficiency or deletion (5-8) consistently have a late onset of dystropathology, by about 8 months of age, with pronounced replacement of myofibers by adipocytes (9). Dysferl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…A characteristic histological feature of dysferlinopathies is the accumulation of fat in skeletal muscles [ 13 , 14 ] and eventually the replacement of muscle fibers by adipose cells [ 4 ]. Since we have previously found high activity of Cx HCs in a dysferlin deficient human cell line [ 5 ] and dysferlin deficient patients and skeletal muscles of blAJ mice present fat accumulation [ 13 , 14 , 15 ], we speculated that some muscle precursor cells might acquire adipogenic commitment due to the elevated Cx HC activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A characteristic histological feature of dysferlinopathies is the accumulation of fat in skeletal muscles [ 13 , 14 ] and eventually the replacement of muscle fibers by adipose cells [ 4 ]. Since we have previously found high activity of Cx HCs in a dysferlin deficient human cell line [ 5 ] and dysferlin deficient patients and skeletal muscles of blAJ mice present fat accumulation [ 13 , 14 , 15 ], we speculated that some muscle precursor cells might acquire adipogenic commitment due to the elevated Cx HC activity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the involvement of an additional and critical pathological mechanism in muscular degeneration remains unknown. A peculiar change of dysferlin deficient skeletal muscles that remains without explanation is the accumulation of fat tissue [ 3 , 4 ]. In this regard, we have suggested that de novo expression of connexin hemichannels (Cx HCs) might participate in muscle changes of dysferlinopathies as a plausible hypothesis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being a member of the ferlin family, dysferlin plays a key role in the active process of repairing muscle membrane lesions and can be widely expressed in a variety of tissues and cells, including skeletal and cardiac muscles, lung, kidney, brain, adipocytes and monocytes 23,24 . Being involved in T‐tubule formation and myogenesis, dysferlin contains a short carboxy‐terminal transmembrane domain and seven amino‐terminal C2 domains (C2A‐C2G) with a DYSF domain localized between C2C and C2D, among which the C2A domain binds to phospholipids in the form of Ca 2+ dependence 25–29 . Patients with LGMD2B may have deficient or absent dysferlin as a result of variants in the DYSF gene.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory exchange ratio was calculated as VCO 2 /VO 2 . Energy expenditure was calculated from VO 2 and respiratory exchange ratio using Weir constants and normalized to lean mass 24 . Food and water intake were recorded every 15 min.…”
Section: Methodsmentioning
confidence: 99%